2021
DOI: 10.3389/fimmu.2021.690817
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Interleukin 10 Deficiency on Intestinal Epithelium Responses to Inflammatory Signals

Abstract: Interleukin 10 (IL-10) is a pleiotropic, anti-inflammatory cytokine that has a major protective role in the intestine. Although its production by cells of the innate and adaptive immune system has been extensively studied, its intrinsic role in intestinal epithelial cells is poorly understood. In this study, we utilised both ATAC sequencing and RNA sequencing to define the transcriptional response of murine enteroids to tumour necrosis factor (TNF). We identified that the key early phase drivers of the transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 96 publications
(107 reference statements)
4
15
0
Order By: Relevance
“…TNF injection induced the transcription of Tnf in the intestinal epithelium of wild-type mice, a result similar to that which others, and our group, have reported previously [ 24 , 31 , 48 ]. There was clear impairment of Tnf mRNA induction in Il10 −/− small intestinal tissue, supporting our earlier in vitro studies where we clearly showed defective TNF-induced transcriptional activation of the Tnf gene in IL-10-deficient intestinal epithelium [ 24 ]. Real-time qPCR results were further validated by the measurement of TNF protein levels, which showed a 50% reduction in intestinal tissue lysates taken from IL-10-deficient mice compared to the wild-type controls.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…TNF injection induced the transcription of Tnf in the intestinal epithelium of wild-type mice, a result similar to that which others, and our group, have reported previously [ 24 , 31 , 48 ]. There was clear impairment of Tnf mRNA induction in Il10 −/− small intestinal tissue, supporting our earlier in vitro studies where we clearly showed defective TNF-induced transcriptional activation of the Tnf gene in IL-10-deficient intestinal epithelium [ 24 ]. Real-time qPCR results were further validated by the measurement of TNF protein levels, which showed a 50% reduction in intestinal tissue lysates taken from IL-10-deficient mice compared to the wild-type controls.…”
Section: Discussionsupporting
confidence: 91%
“…Interleukin-10 is considered a classical anti-inflammatory cytokine that downregulates pro-inflammatory pathways, including activation of NF κ B in immune cells such as macrophages and dendritic cells [ 29 ]. We recently showed that epithelium-derived IL-10 appears to be a positive regulator of NF κ B in vitro, supporting its role as a major regulator of intestinal homeostasis [ 24 ]. Here, in the current study, we utilized IL-10-deficient mice to evaluate further the role of IL-10 within the intestinal epithelium in a TNF-induced in vivo model of inflammation that impacts on intestinal homeostasis [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, nocturnal hypercapnia and sleep fragmentation in patients with OSA also results in the activation of pro-in ammatory pathways and the down-regulation of anti-in ammatory proteins [11]. IL-10 is a pleiotropic cytokine mainly secreted by Th2 helper cells, which can widely inhibit the body's in ammatory response [14]. Gozal, et al [11] demonstrated that the circulating IL-10 levels in children with OSA was lower than that of the control group.…”
Section: Discussionmentioning
confidence: 99%